ANALYSIS OF FACTORS INFLUENCING GREEN PURCHASE BEHAVIOR : A CASE STUDY OF THE COSMETICS INDUSTRY IN INDONESIA - Wilson, Nicholas; Theodorus, Evan; Tan, Pauline (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2018)
This research attempted to uncover factors which could influence consumer’s green purchase behavior towards green cosmetic product in the Indonesian cosmetics Industry. Survey method was used in this research, in which questionnaires were distributed to 260 respondents who have ever bought and used green cosmetics products in Indonesia. Data were then analyzed using AMOS 22.0. Based on the results obtained in this research, it was concluded that attitude towards the behavior and perceived behavioral control had a positive impact on behavioral intention, while perceived behavioral control also had a positive impact toward consumers’ green purchase behavior. Meanwhile, behavioral intention didn’t have a positive impact on green purchase behavior. In regards to the value or implication generated in this research, the results of this research will improve academicians, practicioners, and public’s knowledge and understanding about the factors which had a positive relationship or impact on Indonesian consumers’ green purchase behavior in the cosmetics industry.